Development of a Bio Pocketbook Learning Resource Based on SETS-I (Science, Environment, Technology, Society, and Islamic Integration) to Enhance Students’ Scientific Literacy - Musfirah; Firdaus Daud; Syamsiah; Nurhayati B; Andi Asmawati Azis (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to produce a science learning resource in the form of a SETS-I based (Science, Environment, Technology, Society, and Islamic Integration) Bio Pocketbook that is valid, practical, and effective. The research subjects consisted of expert validators, three teachers, and students, with the product being validated by experts before being tested. This type of research is research and development (R&D), adapted from the ADDIE development model consisting of five stages: analysis, design, development, implementation, and evaluation. Validity data were collected using a product validation questionnaire on the human respiratory system material. Practicality data were obtained through student and teacher response questionnaires, while effectiveness data were collected through a scientific literacy skills test. The results showed that the average overall validity score of the product was in the very high category (1.00). The response results indicated that the product met the criteria of practicality, as the average student response to the product was in the very practical category (92%), and the average teacher response was also in the very practical category (93.75%). The product development also met the effectiveness criteria, as shown by the average N-gain score of each student, which was in the high category (0.73).